Nursing practice and education : aspiring to excellence though seven pillars of learning - Gallagher, Ann; De Luca, Enrico; Deering, Kris (London ; New York, New York : Routledge, 2024)
"This accessible co-produced textbook presents essential knowledge, skills and values relevant to all undergraduate student nurses up to Masters' level. The chapters include a range of features to help readers apply their learning, including the application of relevant international research and incorporating the voices of students, patients and nurse educators. It enables readers to gain confidence and competence in their practice and serves as an important introduction for student nurses"--
Includes bibliographical references and index.
Keywords: Nursing -- Textbooks